Anura diversity and distribution at the three anthropogenic habitat areas of the IPB Dramaga Campus, West Java, Indonesia - Chairunisa Anwar; Nur Azizah Maulidiyah Rahma; Ninda Luqya Nakadira; Septiany Anugrah Kadang; Rahmat Agung Munggaran; Puji Rianti (LPPM Universitas Negeri Jakarta, 2025)
Anura, a group of amphibians widely distributed in freshwater and terrestrial ecosystems, has been understudied regarding its diversity and distribution patterns in urban terrestrial settings. This study aims to identify the species composition, diversity, evenness distribution patterns and environmental correlates of Anura across three differing disturbance level areas within the IPB Dramaga campus in Bogor. Data was collected using the Visual Encounter Survey method. The results indicate that Anura distribution across the three habitats tends to be clustered, comprising 199 individuals from six species and four families. Duttaphrynus melanostictus dominated habitats with high disturbance levels, highlighting its ecological significance as a tolerant species capable of surviving and dominating amphibian communities in disturbed areas. Conversely, the low-disturbance area exhibited the highest species diversity (H′ = 1.13) and evenness (E = 0.63) compared to the other two habitats, supported by an average soil pH of 5.09 and soil moisture of 59.8%. Environmental factors and human activities likely influenced differences in community structure. These findings emphasize the importance of maintaining diverse microhabitats in urban areas to support the persistence of both disturbance-tolerant and sensitive amphibian species.